A prospective comparison of costs between robotics, laparoscopy, and laparotomy in endometrial cancer among women with Class III obesity or higher. Issue 4 (14th December 2021) - Kosa, Sarah D.; Ferguson, Sarah E.; Panzarella, Tony; Lau, Susie; Abitbol, Jeremie; Samouëlian, Vanessa; Giede, Christopher; Steed, Helen; Renkosinski, Benjamin; Gien, Lilian T.; Bernardini, Marcus Q.
Abstract: Background and Objectives: To compare the immediate operating room (OR), inpatient, and overall costs between three surgical modalities among women with endometrial cancer (EC) and Class III obesity or higher. Methods: A multicentre prospective observational study examined outcomes of women, with early stage EC, treated surgically. Resource use was collected for OR costs including OR time, equipment, and inpatient costs. Median OR, inpatient, and overall costs across surgical modalities were analyzed using an Independent‐Samples Kruskal–Wallis Test among patients with BMI ≥ 40. Results: Out of 520 women, 103 had a BMI ≥ 40. Among women with BMI ≥ 40: median OR costs were 4197.02 for laparotomy, 5524.63 for non‐robotic assisted laparoscopy, and 7225.16 for robotic‐assisted laparoscopy ( p < 0.001) and median inpatient costs were 5584.28 for laparotomy, 3042.07 for non‐robotic assisted laparoscopy, and 1794.51 for robotic‐assisted laparoscopy ( p < 0.001). There were no statistically significant differences in the median overall costs: 10 291.50 for laparotomy, 8412.63 for non‐robotic assisted laparoscopy, and 9002.48 for robotic‐assisted laparoscopy ( p = 0.185). Conclusion: There was no difference in overall costs between the three surgical modalities in patient with BMI ≥ 40. Given the similar costs, any form of minimally invasive surgery should be promoted in this population.